Avicenna on Immortality, Pre-existence and the Transmigration of Souls. The Analysis of De Anima, V, 3-4. - Grzeszczak, Jan (Filozofia Chrześcijańska, 2010)
Written probably between 1021-1024 the treatise on soul, known as Liber de Anima or Liber Sextus de Naturalibus, is one of the most popular works of Avicenna in the Middle Ages. It constitutes an original synthesis of the science of the soul, maintained in the peripatetic and neo- Platonic spirit. In book V Avicenna opposes pre-existence and the transmigration of souls. He provides numerous arguments in favour of the immortality of the soul. In this way he breaks away from the typically Greek understanding of the problem of soul. The basis of argumentation for the immortality of the soul is its unity with the body treated as accident. The treatise on soul was received with kindness and interest by scholastics, particularly by Albert the Great. It includes ideas characteristic for Avicenna ideas, for example the story about the Flying Man resembling Cartesian cogito.